Identification and Regulation of TCRαβ+CD8αα+ Intraepithelial Lymphocytes in Murine Oral Mucosa - Wu, Ruiqing; Zhang, Dunfang; Zanvit, Peter; Jin, Wenwen; Wang, Hao; Chen, WanJun (Frontiers in Immunology, 2020)
TCRαβ+CD8αα+ intraepithelial lymphocytes (IELs) are abundant in gastrointestinal (GI) tract and play an important role in regulation of mucosal immunity and tolerance in the gut. However, it is unknown whether TCRαβ+CD8αα+ IELs exist in the oral mucosa and if yes, what controls their development. We here identified and characterized TCRαβ+CD8αα+ IELs from the murine oral mucosa. We showed that the number and function of TCRαβ+CD8αα+ IELs were regulated by TGF-β. We further revealed that oral TCRαβ+CD8αα+ IELs could be altered under systemic inflammatory conditions and by antibiotic treatment at the neonatal age of the mice. Our findings have revealed a previously unrecognized population of oral IELs that may regulate oral mucosal immune responses.